Geographical tradition and reception: Strabo’s ’Geography’ in the context of the Principate - de Aquino Silva, Guilherme (Romanitas - Revista de Estudos Grecolatinos, 2023)
Strabo’s Geography, written between the 1st century BC and AD is a work composed of seventeen books, in which the autor gathered a serie of information about the regions bathed by the Mediterranean. Through Geography, we access data about local nature (climate, relief, soil, rivers, animals and plants), ethnographic aspects (physical appearance, uses and customs, clothing and organization of society), as well as mythological narratives and of historical events. In this article, we presente aspects related to the production, targed audience, geographical tradition and reception of Geography. Therefore, based on our analysis, we will be able to see how Strabo dialogue with his predecessors, in addition to being directly influenced by the context in which he lived.